Harry Potter and the Chamber of Secrets [Illustrated] - Rowling, J. K.; Kay, Jim; Rowling, J. K. (New York : Arthur A. Levine Books, 2016)
When the Chamber of Secrets is opened again at the Hogwarts School of Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
Sequel to: Harry Potter and the sorcerer's stone.
6.7
3-6
Year 2.
940L
V
Keywords: Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; England -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Fiction; School stories; Fantasy fiction; Witches -- Fiction; Potter, Harry, -- (Fictitious character) -- Fiction; Potter, Harry, -- (Fictitious character) -- Juvenile literature; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction